Mecha-Ude. Mechanical arms, 1 - Koyoka, Yoshino (Mecha-ude, 2025)
"Kita-Kagami City is a pretty normal town...except that some people have gotten their hands on Mecha-Ude: powerful, sentient, mechanical beings that attached themselves to their human hosts and have awesome capabilities. When middle-school kid Hikaru accidentally activates Alma, a Mecha-Ude with no memory of its past, they must team up to uncover the mystery of Alma's identity and prevent the powerful Mecha-Ude from ending up in the wrong hands."--